Eggshell bitumen – Alternative binder for road construction - Cui Ming, Ng; Putra Jaya, Ramadhansyah; Haryati, Awang; Khairil Azman, Masri; Noram Irwan, Ramli (2021)
Eggshells are widely used in our country and usually thrown away as waste by consumers. Disposal of the waste eggshell is a serious environmental concern because its needs a lot of landfills and the eggshell waste will release the unpleasant smell. As a result, recycling eggshell into a useful product may provide potential benefits for the food manufacturers and construction industry. Therefore, the potential of eggshell as alternative modified binder was presented in this study.